2021
DOI: 10.3390/su13042388
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Firm Performance in China’s Manufacturing: A Global Perspective of Business Models

Abstract: In a globalized and digital world, manufacturing firms have used internet technology to conduct value appropriation (VA). However, during the COVID-19 crisis, export-led manufacturing firms around the world, particularly those in developing countries, have been forced to lay off workers and cope with VA-related problems, and serious survival problems have resulted in critical corporate social responsibility (CSR)-related challenges. Whereas limited research has discussed relevant issues in nonwestern contexts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
(84 reference statements)
1
25
0
Order By: Relevance
“…The model supports the continuous collection of identified threat behaviors from intrusion detection systems, filtering and analyzing threats in time snapshots, and re-evaluating the security countermeasures, including security administrator (S-Admin), managers, and security management system as stakeholders. Hu et al ( 2021 ) pointed out that during the COVID-19 crisis, export-oriented manufacturing companies worldwide, especially manufacturing enterprises in developing countries, were forced to lay off workers and deal with problems related to value distribution. Serious survival problems led to major challenges related to corporate social responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…The model supports the continuous collection of identified threat behaviors from intrusion detection systems, filtering and analyzing threats in time snapshots, and re-evaluating the security countermeasures, including security administrator (S-Admin), managers, and security management system as stakeholders. Hu et al ( 2021 ) pointed out that during the COVID-19 crisis, export-oriented manufacturing companies worldwide, especially manufacturing enterprises in developing countries, were forced to lay off workers and deal with problems related to value distribution. Serious survival problems led to major challenges related to corporate social responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies, solutions, best practices, and forums reported in the literature that are related to digital transformation in the academic world. For example, researchers report that digital transformation is a company transformation that develops new business models [5] and that digital transformation creates and obtains value by implementing new business architecture [6]. However, most of the research is only an update of digital technology and tool applications, or even just a presentation of new concepts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to previous studies [58][59][60], the regression models also control the following variables: Size is defined as above; Lev is the ratio of asset-liability, which is expressed by the total liabilities divided by the total assets; Growth is operating income growth rate, which is the increase amount of annual operating revenue scaled by the amount of operating revenue last year; Employee is expressed by the natural logarithm of total number of employees; Cash represents cash holdings of the corporate, which is expressed by the natural logarithm of amount of cash and cash equivalents held at the end of the period; Large10 is the equity ratio of the ten largest shareholders. The main variable definitions are shown in Appendix A.…”
Section: Measurement Of Control Variablesmentioning
confidence: 96%
“…This test is mainly to distinguish between companies' efforts to promote the employment of people with disabilities and other CSR behaviors. As discussed above, many studies have focused on the firm performance implications of CSR activities, while most studies have confirmed that CSR will have a significant positive impact on firm performance [43][44][45][46]57,59]. Corporate social responsibility activities will produce a reputation effect [43,44] and improve the relationship with other stakeholders such as government and consumers [47,48], which is often related to higher financial performance.…”
Section: Considering Other Csr Behaviormentioning
confidence: 99%